When the Islamic State kills: ironies of American and ISIS executions - Kaplan, Paul (Critical criminology, 2022)
These research notes explore the idea of comparing executions in the United States (US) to executions undertaken by the Islamic State of Iraq and Syria (ISIS). Is it possible that America’s ostensibly rational, formal, and "clinical" death penalty is more painful for its victims than ISIS victims? I investigate this question by considering the suffering caused by the death penalty in the US, making some informed speculations about ISIS executions, discussing execution in two influential Islamic nations, and observing some ironies these topic raise about the rule of law and capital punishment. My goal with these notes is to spur interest in comparative research on state violence and the death penalty.